Portmanteau words of English food and beverage’s names in Indonesia - Sari, Sulhizah Wulan; Martiwi, Rini; Nisa, Baiatun (Linguistics and Culture Review, 2021)
This study aims to identify the structure of portmanteau words of English food and beverage names in linguistic and relates to cultural views. Descriptive qualitative is applied to this research by finding several data in Supermarket, Mall, Café, Restaurant, and Websites in Indonesia. They are 37 collected data of the portmanteau words that have been earned from March up to July 2020. It is analyzed by revealing their formations in the linguistic concept of word formation (blending), which is proposed by Böhmerová theory and relates to the cultural aspect. The results show that the blending types of English food and beverage's names are fused and the telescoped blend. Those combinations of blending word structures are determinative and coordinative noun. Linguistically, the relation of the portmanteau words of food and beverages name to cultural aspects is entailed in the borrowing word. Those relations represent global food identity as the output of culture formed by the English language. This study is essential not only to develop new vocabularies through the word-formation of blending in the study of linguistic but also its relation to the cultural aspect.